Faktor-faktor yang Mempengaruhi Suku Bunga Pinjaman Perumahan - Prasetyo, Bagus Dwi; Soesilo, Nining Indroyono (Jurnal Kebijakan Ekonomi, 2022)
This study examines the causes of high and low mortgage rates in a country using panel data from 17 countries in Asia (China, Hong Kong, Indonesia, India, Japan, Singapore, South Korea, Thailand), Australia (Australia), Europe (France, Germany, Italy, Spain, United Kingdom) and America (Canada, United States) to see how conditions are in these countries and their institutional housing finance system. By assuming that there is a simultaneous relationship at the mortgage rates which is a two-way relationship, where the dependent variable has an influence on the independent variable. The estimation results of the model using the simultaneous equation also show that in almost all countries studied, the majority of housing finance is using banks as the institutions that provide housing loans, the three-stage least square analysis that is carried out confirms this simultaneously between developed and developing countries where the source of funds, profit, efficiency and volatility of interest rates and inflation have an effect on the ups and downs of the mortgage rate on the supply side. On the demand side, differences in conditions in developed and developing countries also produce different results where simultaneously economic growth, population growth has a significant effect, but on the other hand housing loans, urban population, inflation, house price index are only influential in developed countries, while the exchange rate only affects developing countries. Furthermore, the availability of funds with low yields, increased efficiency of government intervention and public awareness are some of the implications that need to be taken from the results of this study